(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Ritual slaughter regulation involves several interests: freedom of religion expression, animal welfare, market freedom and consumer protection. The analysis of the jurisprudence on this item is meaningful of all the problems the Courts and the legislators have to confront balancing different rights. In the European context a progressive attention is arising toward the animal welfare and a consequent limitation of freedom of religion. Recently, the analysis of the European and comparative jurisprudence highlights the increasing importance given to the transparency of the production process and to the role of a well informed consumer.